Sinkhole risk modeling in residential area using GIS technique - Mohd. Saat, Sa’adiah; Setan, Halim; Matori, Abd. Nasir (2005)
This study presents the development of an Integrated Geographical Information System (GIS), Geophysical Method and Global Positioning Systems (GPS) survey for sinkhole risk modeling in selected residential area. The sinkhole phenomena in residential area have been known to be related to geological factor, environmental and local activities. To determine the subsurface structure and also the location of sinkholes of the study area, the geophysical survey which is resistivity survey was carried out by using ABEM SAS 4000. From the resistivity survey, the area that was identified to have sinkhole was tagged using GPS coordinates through GPS survey using GPS Topcon HiPER. The above data were integrated as a GIS database. Spatial Analysis were carried out using the User Interface developed in this study from the components of ArcGIS Software which are ArcMap and ArcObjects in order to model the sinkhole occurrence risk for the selected residential area. The user interface developed in this study would be useful for those involved in planning and development of housing area and also the other land use activities so that the adverse effect of sinkhole collapse to them could be avoided.